Preliminary results of leaf mineral concentrations for seven pomegranate cultivars grown on calcareous soil - Urlić, Branimir (Array, 2019)
Pomegranate (Punica granatum L.) is one of the traditional fruits cultivated in the Mediterranean part of Croatia with more intensive cultivation in the recent years. The objective of study was to determine leaf nutrient concentrations of seven pomegranate cultivars (five Croatian and two introduced) grown on calcareous soil as leaf nutrient analysis is consider being the best tool for diagnosing fruit tree nutritional status. Significant differences between cultivars have been found for leaf P, Ca, Mg, Fe and Zn concentrations. All cultivars leaf K, Mg, Fe and Zn concentrations were under literature cited thresholds for possible deficiencies, although no visible deficiency symptoms were found. Cultivar Sladun had highest concentration of all determined nutrients and could be possible option for organic and low input cultivation.